Nucleosynthesis Conditions in Outflows of White Dwarfs Collapsing to Neutron Stars - Eirini Batziou; Robert Glas; H.-Thomas Janka; Jakob Ehring; Ernazar Abdikamalov; Oliver Just (The Astrophysical Journal)
An accretion-induced collapse (AIC) or merger-induced collapse (MIC) of white dwarfs (WDs) in binary systems is an interesting path to neutron star (NS) and magnetar formation, alternative to stellar core-collapse and NS mergers. Such events could add a population of compact remnants in globular clusters; they are expected to produce yet unidentified electromagnetic transients including gamma-ray and radio bursts, and to act as sources of transiron elements, neutrinos, and gravitational waves. Here, we present the first long-term (≳5 s postbounce) hydrodynamical simulations in axisymmetry (2D), using an energy- and velocity-dependent three-flavor neutrino transport based on a two-moment scheme. Our set of six models includes initial WD configurations for different masses, central densities, rotation rates, and angular momentum profiles. Our simulations demonstrate that rotation plays a crucial role for the protoneutron star (PNS) evolution and ejecta properties. We find early neutron-rich ejecta and an increasingly proton-rich neutrino-driven wind at later times in a nonrotating model, in agreement with electron-capture supernova models. In contrast to that and different from previous results, our rotating models eject proton-rich material initially and increasingly more neutron-rich matter as time advances, because an extended accretion torus forms around the PNS and feeds neutrino-driven bipolar outflows for many seconds. AIC and MIC events are thus potential sites of r -process element production, which may imply constraints on their occurrence rates. Finally, our simulations neglect the effects of triaxial deformation and magnetic fields, yet they provide valuable reference cases for comparison with future long-term magnetohydrodynamic and 3D AIC studies.